PENGARUH MEDIA POWERPOINT INTERAKTIF TERHADAP HASIL BELAJAR IPA SISWA KELAS IV SDN MARGOREJO 1 - Athour Rohman, Mukhammad; Fanani, Achmad (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine the effect of using interactive PowerPoint media on the science learning outcomes of fourth-grade students at SDN Margorejo 1. This research used an experimental method with a quantitative approach and a non-equivalent posttest-only control group design. Data were collected through observation and posttest results. The data were analyzed using prerequisite tests, namely normality and homogeneity tests, followed by a two-tailed t-test to test the research hypothesis. The results of the study indicate that there is a significant difference in learning outcomes between students taught using interactive PowerPoint media and students taught using conventional methods. Therefore, it can be concluded that the use of interactive PowerPoint media has a significant effect on the science learning outcomes of fourth-grade students at SDN Margorejo 1. Keywords: Interactive PowerPoint Media, Learning Outcomes, Science.